2014
DOI: 10.1080/10601325.2014.936236
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Immobilization of His-Tagged Alcohol Dehydrogenase on Magnetic Nanoparticles in One Step: Application as Biosensor Platform

Abstract: His-tagged Alcohol dehydrogenase was produced as a recombinant protein in E. coli. Afterwards, isolation and immobilization of the enzyme was carried in one-step via copper modified magnetic nanoparticles (MNPs) by the effect of interactions between Cu and histidine. The resulting enzyme bound MNPs was then attached to the surface of carbon paste electrode by the magnetic force and used as an electrochemical biosensor for the alcohol sensing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a recent study, it has been reported that the conversion of a free ADH applied in a BMR dropped to 20 % after just 90 min of operation. 52 Various immobilization approaches [53][54][55] have already been investigated with the goal to improve the enzyme's activity and stability, but none of them have been applied to BMRs.…”
Section: Biocatalytic Membrane Through Immobilization Of Alcohol Dehymentioning
confidence: 99%
“…In a recent study, it has been reported that the conversion of a free ADH applied in a BMR dropped to 20 % after just 90 min of operation. 52 Various immobilization approaches [53][54][55] have already been investigated with the goal to improve the enzyme's activity and stability, but none of them have been applied to BMRs.…”
Section: Biocatalytic Membrane Through Immobilization Of Alcohol Dehymentioning
confidence: 99%